(3fRgI GdWQa aj Yde GdMQas ((3GdfLa s)
(3ChdgG (B:s
(3GdMeO ddg hCUdi hCSde Ydi eMeO hBdg hCSJYjfg aj EKHGJ gPg GdcdeGJ aj GdMQha Ydi GdWQjb GdeYQha s
(3BNQgG (B:s
(3hgh MQa GdLhGH gPG hbO Je eG CQOfG EKHGJg aj gPg GdChQGb Ke s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3HBNQgG aGFOIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdMQha h GdChaGbs